Disposal and replacement practices in Kenya’s smallholder dairy herds - Bebe, B.O.; Udo, H.M.J.; Thorpe, W.R. (International Livestock Research Institute, 2000)
The objectives of this study were to explore the possibilities for improving the breeding practices and developing policies in support of smallholder dairy producers in the central highlands of Kenya through analysing current disposal and replacement practices. Data were obtained from a cross-sectional characterization study. This began with a pilot survey in one district where 365 households were randomly sampled and then extended to another eight districts where 1390 households were randomly sampled. The pooled data from the nine districts comprised 987 dairy households with information on dairy cattle disposal and replacement practices during the previous year and the primary reasons for animal deaths and sales. Complementary information on the origins of cows was collected through targeted surveys of 50 sample households representative of the major dairy systems. Based on farmer recall of events during the year preceding the surveys, almost a third of cow and heifer exits were driven by the households’ needs for cash, and another third resulted from losses caused by diseases. Poor performance was less important, accounting for about 10% of cow exits and about 5% for heifers. More cows (>25% y-1) left the herd in zero- and semi-zero grazing systems than from free-grazing herds (19% y-1) and fewer heifers were available as replacements. As a result, the herds in the more intensive grazing systems would have to purchase replacements to maintain their herd size. By contrast, there were surplus heifer replacements in the free grazing systems. The majority of the breeding cows were born within the herd (68%) and few were purchased: 25% from smallholdings and 7% from large-scale farms. Of the purchased cows, 90% originated from smallholdings and 10% from large-scale farms while 96% of heifers were purchased from smallholdings and only 4% from large-scale farms. Purchases from smallholder farms were from within the locality. The implications of these results for smallholder dairy production in Kenya are discussed.